Assessment of knowledge and attitudes about vaccination in a population of pregnant women and impact of a training program - Aslınur Özkaya Parlakay; Bircan Kayaaslan; Gonca Türker Ergün; Burak Elmas; Vesile Türk; Mehtap Tuğba Dokumacı; Özlem Moraloğlu Tekin (Human Vaccines & Immunotherapeutics)
Vaccination during pregnancy is vital for protecting both maternal and fetal health. A single-center, observational study was conducted with pregnant women attending the antenatal pregnancy school at Ankara City Hospital to assess the effect of maternal immunization training on pregnant women’s knowledge and beliefs about vaccines through pre- and post-training evaluations. Participants completed a 26-item, 3-point Likert questionnaire both before and after a 30-minute training session led by specialist physicians. Changes in response rates for each statement were analyzed. Among 583 enrolled women, 308 completed both questionnaires and were included in the analysis. The median age was 28 years, and 90.6% had at least a high school education. The median gestational age was 34 weeks (range: 8–41), with 79.1% in the third trimester, and 49% were primigravida. Vaccination rates during the current pregnancy was reported by 66.6%, with Td (57.8%) as the most common vaccine, followed by Tdap (11.7%), COVID-19 (3.9%), and influenza (1.6%). Healthcare workers were the primary (92.2%) and most trusted (97.4%) source of vaccine information. Significant changes were observed in 23 of 26 post-training questionnaire statements. The most noticeable increase was related to awareness regarding pertussis and influenza vaccines during pregnancy. Concerns about vaccine-related harm during pregnancy also declined. However, general opposition to vaccination remained unchanged. In conclusion, providing education on immunization to pregnant women can improve vaccine knowledge and dispel misconceptions, offering public health benefits. Integrating these educational sessions into routine antenatal care may improve vaccination rates.